Guideline for the diagnosis and treatment of Faecal Incontinence—A UEG/ESCP/ESNM/ESPCG collaboration. Issue 3 (18th March 2022) - Assmann, Sadé L.; Keszthelyi, Daniel; Kleijnen, Jos; Anastasiou, Foteini; Bradshaw, Elissa; Brannigan, Ann E.; Carrington, Emma V.; Chiarioni, Giuseppe; Ebben, Liora D. A.; Gladman, Marc A.; Maeda, Yasuko; Melenhorst, Jarno; et al.
Abstract: Introduction: The goal of this project was to create an up‐to‐date joint European clinical practice guideline for the diagnosis and treatment of faecal incontinence (FI),  using the best available evidence. These guidelines are intended to help guide all medical professionals treating adult patients with FI (e.g., general practitioners, surgeons, gastroenterologists, other healthcare workers) and any patients who are interested in information regarding the diagnosis and management of FI. Methods: These guidelines have been created in cooperation with members from the United European Gastroenterology (UEG), European Society of Coloproctology (ESCP), European Society of Neurogastroenterology and Motility (ESNM) and the European Society for Primary Care Gastroenterology (ESPCG). These members made up the guideline development group (GDG). Additionally, a patient advisory board (PAB) was created to reflect and comment on the draft guidelines from a patient perspective. Relevant review questions were established by the GDG along with a set of outcomes most important for decision making. A systematic literature search was performed using these review questions and outcomes as a framework. For each predefined review question, the study or studies with the highest level of study design were included. If evidence of a higher‐level study design was available, no lower level of evidence was sought or included. Data from the studies were extracted by two reviewers for each predefined important outcome within each review question. Where possible, forest plots were created. After summarising the results for each review question, a systematic quality assessment using the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) approach was performed. For each review question, we assessed the quality of evidence for every predetermined important outcome. After evidence review and quality assessment were completed, recommendations could be formulated. The wording used for each recommendation was dependent on the level of quality of evidence. Lower levels of evidence resulted in weaker recommendations and higher levels of evidence resulted in stronger recommendations. Recommendations were discussed within the GDG to reach consensus. Results: These guidelines contain 45 recommendations on the classification, diagnosis and management of FI in adult patients. Conclusion: These multidisciplinary European guidelines provide an up‐to‐date comprehensive evidence‐based framework with recommendations on the diagnosis and management of adult patients who suffer from FI. Abstract :